2015
DOI: 10.1186/s12876-015-0360-9
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the role of HLA-DR antigens in Japanese type 1 autoimmune hepatitis

Abstract: BackgroundThe role of HLA-DR antigens in the clinicopathological features of autoimmune hepatitis (AIH) is not clearly understood. We examined the implications of HLA-DR antigens in Japanese AIH, including the effect of HLA-DR4 on the age and pattern of AIH onset, clinicopathological features, and treatment efficacy.MethodsA total of 132 AIH patients consecutively diagnosed and treated in 2000–2014 at 2 major hepatology centers of eastern Tokyo district were the subjects of this study. The frequency of HLA-DR … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
11
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 34 publications
4
11
0
Order By: Relevance
“…In Japan, HLA-DR4 is related to higher levels of serum immunoglobulin G (IgG), the appearance of ASMA,21 and age at the onset of AIH. HLA-DR4 is less frequent in childhood or advanced age (>70 years) 22. In Caucasians, HLA-DR4 is associated with less severity and older age at onset compared to HLA-DR3.…”
Section: Immunogenetic Background Of Aihmentioning
confidence: 99%
“…In Japan, HLA-DR4 is related to higher levels of serum immunoglobulin G (IgG), the appearance of ASMA,21 and age at the onset of AIH. HLA-DR4 is less frequent in childhood or advanced age (>70 years) 22. In Caucasians, HLA-DR4 is associated with less severity and older age at onset compared to HLA-DR3.…”
Section: Immunogenetic Background Of Aihmentioning
confidence: 99%
“…Different risk alleles have been reported in other population cohort of patients with AIH type 1, confirming that there is a well‐identified inter‐population variability in HLA‐associated susceptibility …”
Section: The 81 Ah and Aidsmentioning
confidence: 99%
“…28 Different risk alleles have been reported in other population cohort of patients with AIH type 1, confirming that there is a well-identified inter-population variability in HLAassociated susceptibility. [37][38][39][40][41][42][43] PSC and PBC are rare cholestatic liver diseases characterized by inflammation and fibrosis of intra-and extra hepatic bile ducts. PSC and PBC patients more frequently develop cirrhosis and require for liver transplantation.…”
Section: Autoimmune Liver Diseases: Autoimmune Hepatitis Sclerosinmentioning
confidence: 99%
“…Many studies including a recent genome-wide association study [ 4 ] showed the genetic association of AIH with genes located within human leukocyte antigen ( HLA ) region. HLA - DRB1*03 : 01 and *04 : 01 are associated with AIH in European populations [ 5 ]; *04 : 05 is associated in Japanese and Korean populations [ 6 , 7 , 8 , 9 ]. In addition, several studies have shown that DRB1*04 : 04 , *04 : 05 , and *13 : 01 are associated with AIH in Latin America [ 10 , 11 , 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%